A Brief Overview of the Cerebrospinal Fluid System and Its Implications for Brain and Spinal Cord Diseases - Wichmann, Thea Overgaard; Damkier, Helle Hasager; Pedersen, Michael (Frontiers in Human Neuroscience, 2022)
A comprehensive understanding of the cerebrospinal fluid (CSF) system is essential for our understanding of health and disease within the central nervous system (CNS). The system of CSF refers to all components involved in CSF production, movement and absorption. In recent years, extensive research has resulted in vastly improved understanding of the CSF system in health and disease. Yet, several aspects remain to be fully clarified, notably along the spinal cord as the preponderance of research has focused on the brain. This review briefly summarizes the CSF system and its implications for CNS diseases, and highlights the knowledge gaps that require further research.